Repurposed Biguanide Drugs in Glioblastoma Exert Antiproliferative Effects via the Inhibition of Intracellular Chloride Channel 1 Activity - Barbieri, Federica; Verduci, Ivan; Carlini, Valentina; Zona, Gianluigi; Pagano, Aldo; Mazzanti, Michele; Florio, Tullio (Frontiers in Oncology, 2019)
The lack of in-depth knowledge about the molecular mediators responsible for glioblastoma (GBM) occurrence and progression, combined with few effective and BBB crossing-targeted compounds, represents a major challenge for the discovery of novel and efficacious drugs for GBM. Among relevant molecular determinants of the aggressive behavior of GBM, chloride intracellular channel 1 (CLIC1) represents an emerging prognostic and predictive biomarker as well as a promising therapeutic target. CLIC1 is a metamorphic protein, co-existing as both soluble cytoplasmic and membrane-associated conformers, with the latter conformation able to act as chloride selective ion channel. CLIC1 is involved in several physiological cell functions and its abnormal expression triggers tumor development favoring tumor cell proliferation, invasion, and metastasis. CLIC1 overexpression is associated with aggressive features of various human solid tumors, including GBM, in which its expression level is correlated with poor prognosis. Moreover, increasing evidence shows that modification of ion channel activity, and CLIC1 in particular, in microglia contributes to different neuropathological states and brain tumors. Intriguingly, within GBM cells, CLIC1 is constitutively active specifically within cancer stem cells (CSCs), while it seems less relevant for the survival of non-CSC subpopulations and normal cells. CSCs represent the GBM development and progression driving force, being endowed with stem cell-like properties (self-renewal and differentiation), ability to survive therapies, expand and differentiate to re-initiate tumors. Thus CSCs are the source of the chemo-resistance and relapse rate of GBM. Downregulation of CLIC1 results in drastic inhibition of GBM CSC proliferation in vitro and in vivo, making the control of this channel activity a possible innovative drug target. Recently, drugs belonging to the biguanide class (including metformin) were reported to selectively inhibit CLIC1 activity in CSCs, impairing their viability and invasiveness, but sparing normal stem cells, thus representing potential novel antitumor drugs with a safe toxicological profile. On these premises, we review the most recent insights into the biological role of CLIC1 as a potential selective pharmacological target to obtain better therapeutic responses in GBM. Moreover, we examine old and new drugs able to functionally target CLIC1 activity, discussing the challenges and potential development of CLIC1-targeted therapies.